2021
DOI: 10.21037/atm-21-4528
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and short-term prognostic value of the prognostic nutritional index in cancer: a narrative review

Abstract: Objective: To perform a narrative review of the prognostic value of prognostic nutritional index (PNI) in cancers.Background: Prognostic estimation greatly determines the treatment approach in various cancers. The prognostic nutritional index (PNI), calculated using the serum albumin level and total lymphocyte count, is a useful indicator to assess nutritional and immunological conditions. The PNI represents a low-cost, easy-toperform, noninvasive, rapid, and standardized tool for estimating the prognosis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Different biochemical parameters have been proposed to evaluate the immune-nutritional status such as blood neutrophil, lymphocyte, monocyte, platelet count, neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR), and platelet-lymphocyte ratio (PLR) [34][35][36]. Immune-nutritional scores such as the Prognostic Nutritional Index (PNI) and the Controlling Nutritional Status (CONUT) have also recently been evaluated in human cancer [20][21][22][23][24][25][26]37]. The latter has recently been implemented as a tool of nutritional screening, emerging as an independent prognostic factor for OS in several types of solid tumors [38] as well as in hematological cancer [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Different biochemical parameters have been proposed to evaluate the immune-nutritional status such as blood neutrophil, lymphocyte, monocyte, platelet count, neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR), and platelet-lymphocyte ratio (PLR) [34][35][36]. Immune-nutritional scores such as the Prognostic Nutritional Index (PNI) and the Controlling Nutritional Status (CONUT) have also recently been evaluated in human cancer [20][21][22][23][24][25][26]37]. The latter has recently been implemented as a tool of nutritional screening, emerging as an independent prognostic factor for OS in several types of solid tumors [38] as well as in hematological cancer [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has shown that the PNI is a useful indicator for assessing nutritional and immunological conditions in lung cancer [ 55 ]. PNI is an inexpensive, easy-to-perform, non-invasive, rapid, and standardised tool for estimating cancer prognosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calculated from serum albumin levels and absolute lymphocyte counts, this simple and comprehensive index reflects not only protein stores but also the immunological status. Its prognostic value has been examined in malignancy [ 5 ], autoimmune disease [ 6 ], and heart failure [ 7 12 ] and has been reported in several small-scale studies for patients with acute coronary syndrome (ACS) or stable CAD [ 13 16 ].…”
Section: Backgroudmentioning
confidence: 99%